Stakeholder engagement in the development of genetically modified mosquitoes for malaria control in West Africa: lessons learned from 10 years of Target Malaria’s work in Mali - Dicko, Bakara; Kodio, Souleymane; Samoura, Hatouma; Traoré, Fatoumata; Sykes, Naima; Drabo, Mouhamed; Thizy, Delphine; Coche, Isabelle; Robinson, Benjamin; Sanogo, Kadiatou; Yagouré, Bilkissou; Diop, Samba; et al. (Frontiers in Bioengineering and Biotechnology, 2024)
From 2012 to 2023, the Malaria Research and Training Center (MRTC), based out of the University of Sciences, Techniques and Technologies of Bamako (USTTB), was part of the Target Malaria research consortium working towards developing novel gene drive-based tools for controlling populations of malaria vector mosquitoes.As part of this work, Target Malaria Mali has undertaken a range of in-depth engagement activities with the communities where their research is conducted and with other stakeholders nationally. These activities were meant to ensure that the project's activities took place with the agreement of those communities, and that those communities were able to play a role in shaping the project's approach to ensure that its eventual outcomes were in line with their needs and concerns. This paper aims to conduct a critical assessment of those ten years of stakeholder engagement in order to identify good practices which can inform future engagement work on gene drive research in West Africa. It sets out a range of approaches and practices that enabled the Target Malaria Mali team to engage a variety of stakeholders, to share information, collect feedback, and determine community agreement, in a manner that was inclusive, effective, and culturally appropriate. These can be useful tools for those working on gene drive research and other area-wide vector control methods in West African contexts to ensure that their research is aligned with the interests of the communities who are intended to be its ultimate beneficiaries, and to allow those communities to play a meaningful role in the research process.